Needs Analysis of Authentic Electronic Assessment Based on Critical Thinking Abilities Integrated with Education for Sustainable Development in Measurement Topic - Salma Nur Hamidah; Emiliannur Emiliannur; Festiyed Festiyed; Hayyu Yumna; Lukman Hakim; Nanang Winarno (Universitas Negeri Padang in collaboration with Association of Mathematics and Natural Sciences Institution for Education of Teaching Staff Indonesia (AMLI), 2026)
We cannot avoid technological developments in the 21st century. The development of technology is evenly distributed and increasingly prevalent in every field of life, including in the field of Education. In 21st century education, technology has become the main complement to the learning process. 21st century learning focuses on student center learning which aims to improve four learning competencies, namely critical thinking, cooperation, communication, and creative thinking (4C Skills). One of the abilities expected in the 21st century is critical thinking. This study aims to analyze the need for the creation of authentic e-assessments based on ESD-integrated critical thinking skills in measurement materials. This study uses a qualitative descriptive approach with the Research and Development (R&D) method of the 4-D model at the definition stage. The research subjects consisted of 26 students of SMAN 1 Nan Sabaris who were selected using purposive sampling techniques. The object of the research is in the form of an authentic e-assessment based on critical thinking skills and integrated ESD Measurement Material. Data collection techniques include questionnaires of student needs, teacher interviews, and critical thinking ability tests. The test results show that students' critical thinking skills are still relatively low with an average percentage of 27.88%. In schools, teachers still tend to carry out conventional assessments that are not authentic, have not been integrated with Education for Sustainable Development (ESD), have not assessed critical thinking skills, and have not made optimal use of digital media.